Creative industries agglomeration, regional innovation and productivity growth in China - Hong, Jin; Wentao, Yu; Guo, Xiumei; Zhao, Dingtao (Springer, 2013)
This paper falls into the broad area of economic geography and economics of creativity, and it presents an alternative approach to explain why total factor productivity (TFP) growth is different across China's regions. It establishes an empirical model to estimate the spatial agglomeration effects of creative industries on regional TFP growth, using China's provincial panel data during the period of 2003 to 2010. We found that the creative industries agglomeration (CIA) has significant and positive impact on regional TFP growth. The result also implies that the CIA can facilitate regional TFP growth through promoting regional innovation instead of improving regional efficiency. Therefore, we argue that policy makers should take some measures to retain and establish more creative zones.